The Effect of Job Characteristics, Work Facilities and Motivation on Lecturer Performance at Universitas Nahdlatul Ulama Sumatera Utara - Pohan, Fatimah (International Publisher (YAPENBI), 2025)
This study aims to analyze the influence of job characteristics, work facilities, and work motivation on lecturer performance at Universitas Nahdlatul Ulama Sumatera Utara. The research employed a quantitative associative approach with a total sampling technique involving 60 lecturers as respondents. Data were collected using questionnaires and analyzed using multiple linear regression with SPSS version 20. The results show that job characteristics, work facilities, and motivation have a positive and significant effect on lecturer performance both partially and simultaneously. Job characteristics influence performance by improving task clarity, autonomy, and responsibility. Work facilities, although not yet fully adequate, still support lecturers in performing their duties effectively. Meanwhile, motivation driven by religious values and sincerity enhances creativity and dedication in developing the university. The coefficient of determination (R²) of 0.446 indicates that 44.6% of the variation in lecturer performance is explained by these three variables. The findings suggest that effective management of job design, facility improvement, and motivation enhancement can strengthen overall performance. The study recommends that future research include other organizational and individual factors to provide a deeper understanding of performance determinants in higher education institutions.